Global Uniqueness Results for Fractional Order Partial Hyperbolic Functional Differential Equations - Benchohra Mouffak (Advances in Difference Equations, 2011)
Abstract We investigate the global existence and uniqueness of solutions for some classes of partial hyperbolic differential equations involving the Caputo fractional derivative with finite and infinite delays. The existence results are obtained by applying some suitable fixed point theorems.